Effects of Plant Growth Promoter on Growth Response and Yield of Several Sorghum Varieties in Sukoharjo - Wahyu Anggita Ferdifta; Harsono Puji; Tetrani Sakya Amalia (E3S Web of Conferences, 2022)
Sorghum bicolor is a C4 crop and cereal that is drought tolerant. Sorghum cultivation has several advantages because it requires very little agricultural input. Sukoharjo Regency has dry land and grumusol soil types located in areas with limited water sources, with physical properties of the soil being hard when dry. The experiment is randomized block design with 2 treatment factors. The first treatment was varieties of sorghum (V1=Numbu, V2=Super 1, V3=Suri 3, V4=Keller, V5+Kawali, V6=Black Sorghum, and V7=Bioguma 2). The second treatment was a type of plant growth promoter (no treatment, Auxin 10 ml.L-1 and Gibberellins 10 ml.L-1) and was repeated 3 times. The observation variables as plant height 6 weeks after planting, number of leaves 6 weeks after planting, stem diameter 4 weeks after planting, and seed weight per plans. The result showed the interaction between varieties and applications of plant growth promoter on the number of leave. Bioguma 2 and Super 1 variety had a significant effect on plant height and seed weight per plant.